Exploring Students’ Difficulties in Solving Nonhomogeneous 2nd Order Ordinary Differential Equations with Initial Value Problems - Ningsih, Yunika Lestaria; Mulbasari, Anggria Septiani (Universitas Islam Raden Intan Lampung, INDONESIA, 2019)
This research aims to explore students’ difficulties in resolving Nonhomogeneous 2nd Order Ordinary Differential Equations with initial value problems. The method that can be used to solve this equation is the undetermined coefficient and the Laplace transformation. This research is used descriptive method. The subjects of this study were 73 students in the second year of the Mathematics Education. Data is collected through tests and interviews. Data were analyzed descriptive qualitative. The results of data analysis show that in undetermined coefficient method, students difficult in determining the particular solution of non-homogeneous second-order ordinary differential equations. This is due to student errors in the first step especially in determining the characteristics equation. Whereas, for the Laplace transformation method, students most difficulties are in the step of solving the subsidiary equation. This is due to the weakness of students in completing arithmetic operations in the form of fractions and partial fractions.